2010
DOI: 10.3201/eid1605.090851
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-ResistantStaphylococcus aureusCarriage and Risk Factors for Skin Infections, Southwestern Alaska, USA

Abstract: Skin infection risk was increased among MRSA nasal carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
(34 reference statements)
0
19
0
Order By: Relevance
“…S. aureus carriage has not been reported previously in this Australian population, and Alaskan reports are from a community with high rates of methicillin-resistant S. aureus infection [17]. In other populations, S. aureus carriage is high in infants <3-months of age, but declines rapidly as carriage of the other three bacteria increases, reaching a low point at 1–2 years [18], [19].…”
Section: Discussionmentioning
confidence: 61%
“…S. aureus carriage has not been reported previously in this Australian population, and Alaskan reports are from a community with high rates of methicillin-resistant S. aureus infection [17]. In other populations, S. aureus carriage is high in infants <3-months of age, but declines rapidly as carriage of the other three bacteria increases, reaching a low point at 1–2 years [18], [19].…”
Section: Discussionmentioning
confidence: 61%
“…However, there is a paucity of data regarding this relationship. Stevens et al 19 reported higher rates of subsequent skin and soft tissue infections among MRSA colonized subjects but the magnitude of this difference decreased with time. Nasal MRSA colonization was only positive on admission in 67% of patients admitted with confirmed MRSA infections in a study by Robicsek et al 20.…”
Section: Pathophysiology: Colonization To Infectionmentioning
confidence: 97%
“…Nasal or mucocutaneous colonisation with MRSA is a potential reservoir for infection in the individual patient as well as transmission to other patients and healthcare workers [28][29][30]. However, it has been argued that nasal carriage may not be the main acquisition pathway for SSIs [31,32].…”
Section: Active Screening Of Mrsa Carriers: Universal or Targeted?mentioning
confidence: 98%